A case study of motivational factors at the Federal University of Espírito Santo – Alegre campus - de Oliveira, Josiléia Curty; Barbosa, Kézya Lourenço; Hegedus, Clovis Eduardo Nunes (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The purpose of this study was to identify the motivational factors that contribute to job satisfaction. Hinging upon Maslow’s Hierarchy of Needs Theory and Herzberg’s Two-Factor Theory, a case study of a descriptive and qualitative nature was carried out, which surveyed factors related to workplace satisfaction at the Federal University of Espírito Santo at Alegre campus. The data were obtained by means of a questionnaire sent via institutional email to the teaching and technical-administrative staff. 73 teachers and 45 technical-administrative staff members answered the questionnaire. The results allowed concluding that, in general, the servants are satisfied with: what they do, stability in the workplace, work environment, autonomy in the work sector, integration of the work team, salary plus benefits and opportunity for professional growth. The motivational factors were deemed as the main ones by the teachers whereas the hygienic factors were the most important for the administrative technicians.